Long-term health benefits of appetite suppressants remain unproven - Paumgartten, Francisco José Roma (Revista de Saúde Pública, 2011)
Because of the increasing prevalence of obesity, prevention and treatment of overweight has become a major public health concern. In addition to diet and exercise, drugs are needed for patients who failed to lose weight with behavioral treatment. The current article aimed to summarize recent concerns on the safety and efficacy of appetite suppressants. Several appetite suppressants have been banned for safety reasons. In 2010, sibutramine was withdrawn from the market because a long-term study showed it increased the risks of cardiovascular events. So far no study with a sufficiently large sample size has demonstrated that appetite suppressants can reduce morbidity and mortality associated with overweight. The withdrawal of sibutramine highlights that guidelines for the evaluation of weight control drugs must be more stringent, and studies on their long-term health benefits are needed prior to their marketing.